2021
DOI: 10.1063/5.0061354
|View full text |Cite
|
Sign up to set email alerts
|

GaN-based power devices: Physics, reliability, and perspectives

Abstract: Over the last decade, gallium nitride has emerged as an excellent material for the fabrication of power devices. Among the semiconductors for which power devices are already available on the market, GaN has the widest energy gap, the largest critical field, the highest saturation velocity, thus representing an excellent material for the fabrication of high speed/high voltage components.The presence of spontaneous and piezoelectric polarization allows to create a 2-dimensional electron gas, with high mobility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
164
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 343 publications
(165 citation statements)
references
References 625 publications
1
164
0
Order By: Relevance
“…[22] The configuration of traps would be changed via decorating with other point defects like O interstitials or Ga vacancies. [6] Similar traps have also been observed by Arehart et al (0.57 eV, 1 Â 10 À15 cm 2 ), [15] Huang et al (0.762 eV, 3.4 Â 10 À16 cm 2 ), [19] and Jin et al (0.57-1.12 eV). [20] The physical mechanism for the degraded gate leakage current should be related to the tunneling assisted by the traps.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…[22] The configuration of traps would be changed via decorating with other point defects like O interstitials or Ga vacancies. [6] Similar traps have also been observed by Arehart et al (0.57 eV, 1 Â 10 À15 cm 2 ), [15] Huang et al (0.762 eV, 3.4 Â 10 À16 cm 2 ), [19] and Jin et al (0.57-1.12 eV). [20] The physical mechanism for the degraded gate leakage current should be related to the tunneling assisted by the traps.…”
Section: Resultssupporting
confidence: 78%
“…A. del Alamo, Y. Polyakov, and G. Meneghesso. [ 4–6 ] In their previous works, inverse piezoelectric effect is the major cause for devices’ degradation under 100 V OFF‐state stress, and permanent lattice damage can be observed by optical or electron microscope after wet etching. It is demonstrated that inverse piezoelectric‐induced degradation can be alleviated by reducing Al content in the AlGaN barrier, by optimizing field plate to counterbalance the strain, and even by introducing an AlGaN back barrier.…”
Section: Introductionmentioning
confidence: 99%
“…The breakdown voltage of the HEMT improved by maintaining a large distance between gate and drain (L GD ). On the other hand, the R on of the device will increase with L GD because R on of the HEMT is the sum of 2DEG channel resistance (R channel ) and gate to drain access resistance (R drain ) described by the following Equation 35 : Rongoodbreak=Rchannelgoodbreak+Rdraingoodbreak=LGWG.1italicqμnsgoodbreak+LitalicGDWG.1italicqμns At breakdown condition, LGD=VitalicBREcrit()Critical electric field. Therefore, Rongoodbreak=1WG1italicqμns()LGgoodbreak+VitalicBREitaliccrit From Equation (), the ON‐resistance is strongly depending on the gate length, and breakdown voltage.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 8A indicates the E‐field distribution of conventional gate HEMT and Figure 8B shows the E‐field distribution of gate field plate HEMT. Impact ionization is the primary source for the breakdown behavior of HEMTs 35 . The high E‐field near the drain side of the gate edge initiates the electron–hole pair generation leads to avalanche multiplication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation